2021
DOI: 10.1007/s00535-021-01788-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for Liver Cirrhosis 2020

Abstract: The first edition of the clinical practice guidelines for liver cirrhosis was published in 2010, and the second edition was published in 2015 by the Japanese Society of Gastroenterology (JSGE). The revised third edition was recently published in 2020. This version has become a joint guideline by the JSGE and the Japan Society of Hepatology (JSH). In addition to the clinical questions (CQs), background questions (BQs) are new items for basic clinical knowledge, and future research questions (FRQs) are newly add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 251 publications
(187 citation statements)
references
References 220 publications
(247 reference statements)
0
179
0
8
Order By: Relevance
“…At present, etiological and symptomatic therapy are the main treatment approaches for liver cirrhosis in clinical settings ( 46 ). For example, antiviral therapy is used to treat hepatitis virus-related cirrhosis, endoscopic variceal ligation is used for treating gastrointestinal bleeding, while transjugular intrahepatic portosystemic stent-shunt is applied for treating refractory ascites and portal hypertension ( 47 ). However, the treatment for protection of hepatocytes remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, etiological and symptomatic therapy are the main treatment approaches for liver cirrhosis in clinical settings ( 46 ). For example, antiviral therapy is used to treat hepatitis virus-related cirrhosis, endoscopic variceal ligation is used for treating gastrointestinal bleeding, while transjugular intrahepatic portosystemic stent-shunt is applied for treating refractory ascites and portal hypertension ( 47 ). However, the treatment for protection of hepatocytes remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…BACCs are associated with activation of the mammalian target of rapamycin pathway and liver injury in mice[ 89 - 91 ]. However, BCAA supplementing can reduce further liver injury in patients with liver cirrhosis[ 92 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…According to the practice guidelines of the American Association for the Study of Liver Diseases and the European Association for the Study of the Liver [22] and the Japanese Society of Gastroenterology and the Japan Society of Hepatology [27], lactulose is the first-choice treatment for overt HE, and rifaximin is an add-on therapy to lactulose for the prevention of overt HE recurrence. Although many studies have reported the usefulness of poorly absorbable oral antibiotics for HE [28][29][30], the pharmacological mechanism of rifaximin is now a subject of debate.…”
Section: Child-pugh Gradementioning
confidence: 99%